ANALISIS RASIO LIKUIDITAS DALAM MEMENUHI KEWAJIBAN PADA PERUSAHAAN DAGANG YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sintiya Bahi; Ilyas Lamuda; Novaliastuti Masiaga (Universitas Bina Taruna Gorontalo, 2024)
The objective of this research is to analyze the liquidity ratio in measuring the company's ability to meet obligations in trading companies listed on the Indonesia Stock Exchange. The usefulness of the research results is expected to contribute to the understanding of solving issues related to the analysis of factors affecting customer loyalty and can be used as a consideration for the companies studied in taking corrective steps for the future. It can also be used as an evaluation material in determining future company strategies. Financial ratio analysis is a part of business or risk prospect analysis for decision-making purposes by evaluating the business environment, strategy, and the company's financial position and performance. The financial statement analyses commonly used by companies include liquidity analysis, solvency analysis, and profitability analysis. Liquidity analysis provides insights into a company's ability to match short-term liabilities maturing with current assets. The liquidity ratio owned by the company can be used as an evaluation material and for the effectiveness of company management. Based on these issues, the author conducted research on